EFEKTIVITAS SANKSI QANUN NOMOR 6 TAHUN 2014 TENTANG TINDAK PIDANA KHAMAR, MAISIR KHALLWAT, ZINA, DAN DAMPAKNYA TERHADAP PERILAKU MASYARAKAT KOTA SUBULUSSALAM - Hafsah, Zakirun, Nawir Yuslem, (AT-TAFAHUM: Journal of Islamic Law, 2017)
Abstract: This research aims to describe the discussion which is formulated in three questions, namely: 1. How is the implementation of Qanun sanctions against the acts of the Khamar, Maisir, Khalwat, and Adultery pidan? 2. How is the implementation of socialization and implementation of Qanun sanctions number 6 of 2014 in the City of Subulussalam? 3. What is the impact on the behavior of Subulussalam City community after the imposition of Qanun sanction number 6 of 2014? This type of research is included in a qualitative descriptive study using the Statute Approach (statutory approach). Data sources from this study were divided into two sources namely primary data sources obtained from interviews with several informants in the field. And Secondary data sources namely data sources obtained through literature study include books, archives, and regulations that are arranged systematically. In general, this study found that Qanun sanction number 6 of 2014 concerning the criminal acts of Khamar, Maisir, Seclusion, and Adultery was already good by regulation. Seen from the rules and sanctions that are complete, as well as the implementation. However, the implementation is still very lacking. This is evidenced by the large number of cases that are not handled. Likewise, the community's knowledge and awareness about qanun sanctions is also very weak, this is caused by the lack of socialization conducted by the Ulama Consultative Council (MPU), Islamic Sharia Service (DSI), SATPOL-PP and WH. As a result, the Jinayat Qanun sanction No. 6 of 2014 did not have an impact on the behavior of the people of Subulussalam City (ineffective).Keywords: Effectiveness, Qanun Sanction, Impact, Behavior.